The effect of electronic word of mouth and travel motivation on revisit intention - Reza Irsyaddillah; Okki Trinanda (Universitas Negeri Padang, 2021)
The purpose of this research was to analyze: (1) Effect of Electronic Word of Mouth on revisit intention at Lubang Mbah Soero, Sawahlunto, and (2) The effect of Travel Motivation on revisit intention at Lubang Mbah Soero, Sawahlunto. A type of this research is causative. This research population was everyvisitors of Lubang Mbah Soero. The sampling technique were used on this research was purposive sampling. Total sample that we used for this research was 160 people. The data that we used for this research are primary and secondary obtained by distributing the questionnaires to visitors. The analytical methode that we used is descriptive and inductive analysis throught multiple regression. The results showed that: (1) Electronic Word of Mouth has significantly positive impact on revisit intention at Lubang Mbah Soero, Sawahlunto, (2) and Travel Motivation has significantly positive impact on revisit intention at Lubang Mbah Soero, Sawahlunto